2019
DOI: 10.1111/prd.12321
|View full text |Cite
|
Sign up to set email alerts
|

Current trends and new developments in HIV research and periodontal diseases

Abstract: With the advent of combined antiretroviral therapies, the face of HIV infection has changed dramatically from a disease with almost certain mortality from serious comorbidities, to a manageable chronic condition with an extended lifespan. In this paper we present the more recent investigations into the epidemiology, microbiology, and pathogenesis of periodontal diseases in patients with HIV, and the effects of combined antiretroviral therapies on the incidence and progression of these diseases both in adults a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 165 publications
0
23
0
Order By: Relevance
“…Patients with HIV or a compromised immune function, represent a group at higher risk of systemic and oral manifestations [91,92]. PD associated with HIV has been studied by several researchers [93][94][95], this possible association has been considered since PD is a source of chronic inflammation [96]. Some authors suggest that HIV is a contributing factor in the prevalence of PD.…”
Section: Hiv (Human Immunodeficiency Virus)mentioning
confidence: 99%
“…Patients with HIV or a compromised immune function, represent a group at higher risk of systemic and oral manifestations [91,92]. PD associated with HIV has been studied by several researchers [93][94][95], this possible association has been considered since PD is a source of chronic inflammation [96]. Some authors suggest that HIV is a contributing factor in the prevalence of PD.…”
Section: Hiv (Human Immunodeficiency Virus)mentioning
confidence: 99%
“…Periodontal diseases are completely within the framework of the potential consequences of HIV [ 6 , 7 ]. They are multifactorial chronic infectious diseases, classically occurring around the age of 35–40 years old and are part of a rationale of co-morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…59 For example, explaining how preventive periodontal treatment and oral hygiene interventions can lead to improvements in systemic inflammation, HIV outcomes, and other co-morbidities associated with HIV can help exemplify how disclosure to dentists is a separate entity from personal disclosure. [60][61][62] Limitations of this study include the collection of selfreported data, so potential information bias must be considered on account of social desirability, which can occur when research subjects participating in self-reported questionnaires provide responses that are considered more socially favorable or underreport responses that are more accurate but socially undesirable. 63 Social desirability bias can be a deterrent against women living with HIV reporting that they had not disclosed their serostatus to a dentist, which could lead to an overestimate of the disclosure percentage.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the decision‐making that precipitates selectivity of disclosure involves calculations of the perceived consequences of informing a particular individual 59 ; as such, it is critical that women living with HIV are informed of the positive implications of disclosing to their dentists as a conduit to preventing dental disease that is distinct from their disclosure to personal relations 59 . For example, explaining how preventive periodontal treatment and oral hygiene interventions can lead to improvements in systemic inflammation, HIV outcomes, and other co‐morbidities associated with HIV can help exemplify how disclosure to dentists is a separate entity from personal disclosure 60–62 …”
Section: Discussionmentioning
confidence: 99%